User Experiences of an Internet-Based Stepped-Care Intervention for Individuals With Cancer and Concurrent Symptoms of Anxiety or Depression (the U-CARE AdultCan Trial): Qualitative Study - Igelström, Helena; Hauffman, Anna; Alfonsson, Sven; Sjöström, Jonas; Cajander, Åsa; Johansson, Birgitta (JMIR Publications, 2020)
BackgroundThe internet-based stepped-care intervention iCAN-DO, used in the multicenter randomized controlled trial AdultCan, was developed for adult patients undergoing treatment for cancer and concurrently experiencing anxiety or depressive symptoms. iCAN-DO aimed to decrease symptoms of anxiety or depression. Step 1 comprises access to a library with psychoeducational material and a peer-support section, as well as the possibility to pose questions to a nurse. Step 2 of the intervention offers treatment consisting of internet-based cognitive behavioral therapy (iCBT) to participants still experiencing anxiety or depression at 1, 4, or 7 months after inclusion. ObjectiveThe study aimed to explore user experiences of delivery, design, and structure of iCAN-DO from the perspective of people with cancer. MethodsWe studied user experiences by interviewing 15 informants individually: 10 women with breast cancer (67%), 4 men with prostate cancer (27%), and 1 man with colorectal cancer (7%) with a mean age 58.9 years (SD 8.9). The interviews focused on informants' perceptions of ease of use and of system design and structure. Informants had been included in iCAN-DO for at least 7 months. They were purposefully selected based on activity in Step 1, participation in iCBT (ie, Step 2), gender, and diagnosis. ResultsOf the 15 informants, 6 had been offered iCBT (40%). All informants used the internet on a daily basis, but 2 (13%) described themselves as very inexperienced computer users. The analysis revealed three subthemes, concerning how user experiences were affected by disease-specific factors and side effects (User experience in the context of cancer), technical problems (Technical struggles require patience and troubleshooting), and the structure and design of iCAN-DO (Appealing and usable, but rather simple). ConclusionsThe results indicate that user experiences were affected by informants' life situations, the technical aspects and the design of iCAN-DO, and informants' preferences. The results have generated some developments feasible to launch during the ongoing study, but if iCAN-DO is to be used beyond research interest, a greater level of tailoring of information, features, and design may be needed to improve user experiences. The use of recurrent questionnaires during the treatment period may highlight an individual's health, but also function as a motivator showing improvements over time.